Bankers' pay structure and risk - Thanassoulis, J (University of Oxford, 2011)
This paper studies the contracting problem between banks and their bankers, embedded in a competitive labour market for banker talent. To motivate effort banks must use some variable remuneration. Such remuneration introduces a risk-shifting problem by creating incentives to inflate early earnings: to manage this some bonus pay is optimally deferred. As competition between banks for bankers rises it becomes more expensive to manage the risk-shifting problem than the moral hazard problem. If competition grows strong enough, contracts which permit some risk-shifting become optimal. Empirically I demonstrate that balance sheets have changed in a manner which triggers this mechanism.